1998
DOI: 10.1111/j.1469-8749.1998.tb15398.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of bilateral motor control in children with developmental coordination disorders

Abstract: This research examined behavioral (i.e. movement time) and neuromuscular (EMG) characteristics of unilateral and bilateral aiming movements of children with normal motor development and children with developmental coordination disorders ( D O ) . Two age groups of children were studied 6 to 7, and 9 to 10 year olds. Bilateral aiming movements involved moving the two hands to targets of either (1) the same amplitude -symmetrical bilateral movements, or (2) different amplitudes -asymmetrical bilateral movements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 40 publications
1
22
0
1
Order By: Relevance
“…Thus, both groups of participants introduced tight couplings between DF to render the movement system controllable. 13,[16][17][18][19] Progress of skill acquisition involves the release of DF. 12,15 This was shown in the AMC group as their elbows became more involved in the task of two-handed catching (Table I; Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, both groups of participants introduced tight couplings between DF to render the movement system controllable. 13,[16][17][18][19] Progress of skill acquisition involves the release of DF. 12,15 This was shown in the AMC group as their elbows became more involved in the task of two-handed catching (Table I; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when initially solving a complex movement problem with redundant DF, children with DCD do so by rigidly coupling their limbs. 7,12,13,16 However, under the assumption that skill acquisition is a process of trying to find ways of controlling the redundant DF and exploiting them during movement coordination, ensuring flexibility of the motor apparatus, 12,13 it appears that children with DCD need help with this process, which may have important implications for intervention. 7 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also suggested that neuromuscular deficits in children with DCD may contribute to their altered balance strategies (Huh et al, 1998;Johnston et al, 2002;Raynor, 2001;Smits-Engelsman, Westenberg, & Duysens, 2008). Their motor impairments typically include lower maximal knee muscle strength and power, increased knee flexor and extensor co-activation (Raynor, 2001); less steady force production (Smits-Engelsman et al, 2008); inconsistent and less efficient motor-control strategies to execute movements (Huh et al, 1998); inconsistent timing of postural muscle activation (Johnston et al, 2002;Williams, 2002); proximal to distal muscle activation patterns; and increased and prolonged activation or co-contraction of the ankle muscles in standing (Geuze, 2003;Williams & Castro, 1997).…”
Section: Postural Control Strategies Among Children With Dcdmentioning
confidence: 96%
“…Their motor impairments typically include lower maximal knee muscle strength and power, increased knee flexor and extensor co-activation (Raynor, 2001); less steady force production (Smits-Engelsman et al, 2008); inconsistent and less efficient motor-control strategies to execute movements (Huh et al, 1998); inconsistent timing of postural muscle activation (Johnston et al, 2002;Williams, 2002); proximal to distal muscle activation patterns; and increased and prolonged activation or co-contraction of the ankle muscles in standing (Geuze, 2003;Williams & Castro, 1997). These may partly explain the ineffective motor strategies demonstrated by our DCD group in more challenging environments.…”
Section: Postural Control Strategies Among Children With Dcdmentioning
confidence: 99%
See 1 more Smart Citation